Enhancing mathematical disposition and learning outcomes through Team Games Tournament: A two-cycle action research on probability instruction in indonesian secondary education - Cintya Mayangsari; Abd Qohar; Nurul Faridha (Nashir Al-Kutub Indonesia, 2025)
Despite growing recognition of mathematical disposition's importance for long-term STEM success, traditional teacher-centered instruction often fails to develop students' affective engagement, leading to mathematics anxiety and diminished self-efficacy. Team Games Tournament (TGT) offers a promising cooperative learning approach, yet systematic investigation of its effects on both cognitive and affective outcomes remains limited. This two-cycle action research investigated TGT implementation effects on probability learning outcomes and mathematical disposition across four NCTM dimensions: attention to accuracy and precision, perseverance in facing challenges, reflection and evaluation abilities, and openness to diverse strategies. Thirty-four Grade 10 students in Aceh, Indonesia, participated in seven-week TGT instruction following Kemmis and McTaggart's spiral model. Data collection employed validated achievement tests (α = 0.82) and mathematical disposition questionnaires (α = 0.89) at three time points, supplemented by classroom observations and field notes. Paired t-tests, effect size calculations, and chi-square analyses examined changes across baseline, Cycle 1, and Cycle 2. TGT implementation produced substantial improvements in achievement (M = 67.3 to 87.7; Cohen's d = 2.35) and mastery rates (32.4% to 88.2%). Mathematical disposition improved markedly, with high-disposition students increasing from 12% to 70%. Iterative refinements in Cycle 2 generated additional significant gains (d = 0.79), demonstrating cumulative benefits of sustained implementation. Dimension-specific analysis revealed differential growth patterns, with tournament structures rapidly developing accuracy attention while strategic flexibility required sustained exposure. Well-designed TGT implementation simultaneously enhances cognitive achievement and cultivates productive mathematical dispositions essential for 21st-century competencies, offering scalable approaches for transforming mathematics instruction in contexts where students exhibit low engagement.